Quality seed production of okra in northern plains of India - Sharma, Vikas; Singh, Vijaypal; Yadav, AC; Duhan, Dharamveer (Vegetable Science, 2012)
Okra [Abelmoschus esculentus (L) Moench] is an important annual vegetable crop propagated through seed in tropical and sub tropical regions of the world. It is grown mainly for its tender green fruits used as vegetable. In Haryana, it is grown twice a year during spring– summer (March-June) and rainy (July -October) seasons. A number of high yielding and good quality varieties are grown in the country, however their quality seed is always in short supply. Seed production technology may vary among cultivars. Hence there is need to develop and standardize the technology for seed production for each of the important cultivars. The seed production in okra is influenced by different sowing time and plant spacing. Therefore, there is an urgent need to find out the suitable sowing time and plant population for good quality seed production of okra var. Hisar Unnat.